Exploring Geometric Conjectures with the Help of a Learning Environment - A Case Study with Pre-Service Teachers (Research Journal of Mathematics & Technology, 2022)
Several researches show the potential of using new information and communication technologies (ICT)in the teaching and learning of mathematics. One of the branches in the teaching of mathematics that,over time, has deserved a special mention, is geometry, namely with the use of dynamic geometrysystems (DGS). A learning environment for teaching and learning geometry, associated with tasks ofan exploratory and investigative nature, tends to favor the discovery of properties and geometricrelationships, which benefits the acquisition of knowledge and the production of evidence. In this articlethe learning environment Web Geometry Laboratory (WGL) was used in a case study for theexploration of visual proofs. The study was done with pre-service teachers. Conclusions are drawn andfuture work is foreseen.